(3TQM bUjOI GdHQOg ddHhUjQis - (3eMeO Hf CMeO Hf eMeO Hf CHi HcQs; (3GdHhUjQj,J (B696 (3g` s ((3GdMGL CMeO Hf GdMGL YKeGf GdNWjH s)
(3ChdgG (B:s
(3hHYO ajbhd Cbd YHGO Gddg eMeO Hf CMeO Hf CHj HcQ ZaQ Gddg dge deG cGfJ GdbUjOg GdehSheg HGdchGcH GdOQjg s
(3BNQgG (B:s
(3GdfZeg jbGd adGf MSf GdfZeg EPG cGf MSf GdUhJ ai GdbQGAI JMJ hHGdNjQ YeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HBNQ UaMGJgG JYbjHgs
(3gcPG hQO hGVMkG ai GdeNWhW hai cTa GdXfhf (B2/ 1333 (3hTQMgG CMeO Hf eMeO Hf CHj HcQ dYdg GdeQYTi GbJUQ Ydi Md CdaGXgG hGFeg ai GdeMQe SfI (B797 (3Ke TQMgG TQMkG eHhWkG ai TYHGf Sfg (B809 (3hSeGg fRgI GdWGdHjf hJMaI GdQGZHjfs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs